Innominate vein reconstruction in patients with bilateral superior vena cava undergoing bilateral bidirectional superior cavopulmonary anastomosis - Sachin Talwar; Niwin George; Afroza Firdaus; Mary H Fanai; Shiv Kumar Choudhary (Wolters Kluwer Medknow Publications, 2023)
A 4.5-year-old patient with tricuspid atresia, pulmonary stenosis, bilateral superior vena cava veins with absent innominate vein, and hypoplasia of the left pulmonary artery required a bidirectional superior cavopulmonary anastomosis. An innominate vein was fashioned out of a 6 mm polytetrafluoroethylene graft. The technique is briefly discussed.